Pengaruh Pertumbuhan Ekonomi, Belanja Bantuan Sosial dan Kesempatan Kerja Terhadap Pengentasan Kemiskinan di Kota Banjarmasin - Rahmaniar Zulfana Putri; Muhammad Effendi (PPJP Universitas Lambung Mangkurat, 2021)
This study aims to determine (1) the effects of economic growth, social assistance and work opportunities simultaneously against poverty reduction in Banjarmasin City and (2) to find out the dominant factor that influence poverty reduction in Banjarmasin City. This research type is quantitative research. While the location of this research is Banjarmasin City, and the object of the research is economic growth, social assistance, work opportunities and poverty in Banjarmasin City in 2009-2018.The results of this study show that Economic Growth, Social Assistance and Work Opportunities at the same time had no effect on Poverty Reduction in Banjarmasin City in 2009-2018. The results of this study show that Economic Growth is the dominant factor that affect Poverty Reduction in Banjarmasin City in 2009-2018.